2014
DOI: 10.1371/journal.pone.0086257
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes Modulate the Polarization of CD4+ T Cells to Th1 Cells

Abstract: T-cell characteristics are dynamic and influenced by multiple factors. To test whether cells and the environment in the central nervous system (CNS) can influence T-cells, we tested if culturing mouse CD4+ T-cells on mouse primary astrocytes, compared with standard feeder cells, modified T-cell polarization to Th1 and Treg subtypes. Astrocytes supported the production of Th1 cells and Tregs, which was diminished by inflammatory activation of astrocytes, and glutamate accumulation that may result from impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 51 publications
3
25
0
Order By: Relevance
“…Expression of three different iGluRs has also been shown on CD4+ T-cells, and their stimulation potentiates activation-induced intracellular calcium mobilization (Lombardi et al 2001). In line with previous results, a recent study has shown that NMDA receptor stimulation on CD4+ Tcells enhances Tbet expression and potentiates IFN-γ production (Beurel et al 2014). Thus, elevated glu levels on PD brain could lead to a neuroinflammatory phenotype on CD4+ T-cells.…”
Section: Neurotransmitters As Modulators Of Encephalitogenic T-cells supporting
confidence: 89%
“…Expression of three different iGluRs has also been shown on CD4+ T-cells, and their stimulation potentiates activation-induced intracellular calcium mobilization (Lombardi et al 2001). In line with previous results, a recent study has shown that NMDA receptor stimulation on CD4+ Tcells enhances Tbet expression and potentiates IFN-γ production (Beurel et al 2014). Thus, elevated glu levels on PD brain could lead to a neuroinflammatory phenotype on CD4+ T-cells.…”
Section: Neurotransmitters As Modulators Of Encephalitogenic T-cells supporting
confidence: 89%
“…Similarly, aligned electrospun nanofibers minimize the host immune reaction, enhance tissue-scaffold integration, and generate a thinner fibrous capsule compared to random fibers and films [32]. Diameter of electrospun fibers modulate the immune reaction, macrophage-mediated release of pro-inflammatory cytokines, and astrocyte-mediated reduction of excitotoxic glutamate [31, 36], the latter of which could promote Treg infiltration and prevent chronic inflammation [37]. …”
Section: 1 Biomaterialsmentioning
confidence: 99%
“…Recent in vitro studies provided clues of the effect of astrocytes on T cells. Eléonore Beure et al found that culturing mouse CD4 + T-cells on mouse primary astrocytes without supplements of additional cytokines modified T-cell polarization to Th1 and Treg subtypes (Beurel et al, 2014). This modified T-cell polarization was diminished by inflammatory activation of astrocytes.…”
Section: Interaction Between Astrocytes and T Cells Under Physiolomentioning
confidence: 99%
“…Besides IL-2, astrocytes might affect T cells via other mechanisms. For example, glutamate promotes Th1 cell production in the presence of anti-IL-4 and IL-12 (Beurel et al, 2014). Addition of glutamate on CD4 + T cells was sufficient to increase T-bet expression.…”
Section: Interaction Between Astrocytes and T Cells Under Physiolomentioning
confidence: 99%